COVID-19: Impact in endothelial function and therapy with Mesenchymal Stromal Cells (2021)
The new pandemic of SARS-CoV-2 Betacoronavirus, has spread worldwide, and infected millions of individuals causing the disease denominated of COVID-19. Further on flu symptoms, due to the high tropism of virus, has most been observed in the COVID-19 pathophysiology: acute heart failure, thromboembolism events, acute renal failure, neurological and liver damage, and multiple organ failure, with special attention to endothelial disfunction. Hence, elucidate whether virus target the endothelium is a crucial step to understand COVID-19 pathogenesis. However, the permissiveness of blood vessels during SARS-CoV-2 infection remains unclear, but regardless endothelial infection, the vascular disfunction may occurred in response to molecular inflammatory signaling triggered by immune cells that attempt to limit infection. Thus, alternative therapies using mesenchymal stromal cells (MSCs) can change this scenario and help critically ill patients. In this reflection, we attempt to discuss COVID-19 pathophysiology with impact in endothelial function and explore the applicability of MSC-based therapies as alternative treatment.